1988
DOI: 10.1243/pime_proc_1988_202_107_02
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pressure Gradient and Freestream Turbulence Intensity on the Length of Transitional Boundary Layers

Abstract: The paper presents the results of an experimental investigation aimed at an elucidation of the individual and collective influence of freestream turbulence intensity and pressure gradient on the length of the transitional boundary layer. A correlation for the transition length Reynolds number is developed and used, in an intermittency-based computational scheme, to predict the transitional boundary layer behaviour in a number of practical flows representative of the suction surface of gas turbine blading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…While the nondimensional formation rate parameter N includes the propagation parameter σ, the very strong dependence of N on pressure gradient indicates that the spot formation rate increases significantly as adverse pressure gradient strengthens. Fraser (1988) found that favorable pressure gradients continue the trend of Figure 15, with the spot formation rate decreasing as the favorable pressure gradient increases. Figure 15: Effect of non-dimensional pressure gradient parameter on spot formation parameter N. (From Gostelow, 1994) …”
Section: Pressure Gradient Effectsmentioning
confidence: 54%
“…While the nondimensional formation rate parameter N includes the propagation parameter σ, the very strong dependence of N on pressure gradient indicates that the spot formation rate increases significantly as adverse pressure gradient strengthens. Fraser (1988) found that favorable pressure gradients continue the trend of Figure 15, with the spot formation rate decreasing as the favorable pressure gradient increases. Figure 15: Effect of non-dimensional pressure gradient parameter on spot formation parameter N. (From Gostelow, 1994) …”
Section: Pressure Gradient Effectsmentioning
confidence: 54%
“…to pressure gradient could be detected. The effects of pressure gradient and free-stream turbulence intensity on the length of transition were further studied by Fraser et al (1988). Their data showed that while the turbulence level remains constant, an increase in the adverse pressure gradient causes a decrease in the transition length Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…The most consistent definition of the state of transition has proved to be the observation of turbulent intermittency. Some measurements of transition in a streamwise pressure gradient, in which observations of intermittency have been reported in addition to the other boundary layer properties, have been made by Narasimha (1957), Abu-Ghannam and Shaw (1980), Fraser, Milne and Gardiner (1988), Ashworth, LaGraff and Schultz (1989) and by Gostelow and Blunden (1988).…”
mentioning
confidence: 99%